Tuning the preferentially electrochemical growth of carbon at the "gaseous CO2-liquid molten salt-solid electrode" three-phase interline. (20th November 2019) - Chen, Xiang; Zhao, Haijia; Xie, Hongwei; Qu, Jiakang; Ding, Xueyong; Geng, Yunfeng; Wang, Dihua; Yin, Huayi
Abstract: It has been widely accepted that the electrochemical reduction of CO2 in molten carbonate is implemented by the reduction of CO3 2− at the cathode that releases O 2− to capture CO2 and replenish CO3 2− . This paper aims to reveal the direct electrochemical reduction of gaseous CO2 in molten salts and the growth behaviors of carbon at the CO2 /molten salt/electrode interline. The electrochemical reduction of gaseous CO2 takes place at the three-phase interline of gaseous CO2 /liquid molten salt/solid electrode (GLS-3PI) when the temperature is over 700 °C. The reduction of CO2 at the GLS-3PI results in the preferential growth of carbon, posing a potential risk to short-circuiting the electrolysis cell. An insulative sheath can prevent the CO2 contacting the GLS-3PI, thereby avoiding the preferential growth of carbon and getting rid of the risk of the short circuit. This paper offers new insights into understanding the direct electrochemical reduction of CO2 at the GLS-3PI and provides an isolation strategy to engineer the molten salt electrolysis cells.